Bibliografske družine v COBIB-U - Petek, Marija (Knjižnica, 2005)
The article deals with bibliographic families in the COBIB online catalogue, their size and complexity. Using a random sample of bibliographic records, relationships among family members are also treated. Bibliographic relationships in the catalogue are not always identified or are expressed only implicitly, therefore data on relationships should be added and the corresponding bibliographic records linked. This would make searching among the different versions of the same item easier, bibliographic retrieval would be improved and the use of library materials made more efficient.
Keywords: knjižnični katalogi; bibliografska družina; bibliografska entiteta; vzajemna katalogizacija